Incomplete immune reconstitution despite virologic suppression in HIV-1 infected children and adolescents. (27th March 2015) - Krogstad, Paul; Patel, Kunjal; Karalius, Brad; Hazra, Rohan; Abzug, Mark J.; Oleske, James; Seage, George R.; Williams, Paige L.; Borkowsky, William; Wiznia, Andrew; Pinto, Jorge; Van Dyke, Russell B.
Abstract : Objectives: Some perinatally infected children do not regain normal CD4 + T-cell counts despite suppression of HIV-1 plasma viremia by antiretroviral therapy (ART). The frequency, severity and significance of these discordant treatment responses remain unclear. Design: We examined the persistence of CD4 + lymphocytopenia despite virologic suppression in 933 children (≥5 years of age) in the USA, Latin America and the Caribbean. Methods: CD4 + T-cell trajectories were examined and Kaplan–Meier methods used to estimate median time to CD4 + T-cell count at least 500 cells/μl. Results: After 1 year of virologic suppression, most (99%) children achieved a CD4 + T-cell count of at least 200 cells/μl, but CD4 + T-cell counts remained below 500 cells/μl after 1 and 2 years of virologic suppression in 14 and 8% of children, respectively. Median times to first CD4 + T-cell count at least 500 cells/μl were 1.29, 0.78 and 0.46 years for children with less than 200, 200–349 and 350–499 cells/μl at the start of virologic suppression. New AIDS-defining events occurred in nine children, including four in the first 6 months of virologic suppression. Other infectious and HIV-related diagnoses occurred more frequently and across a wide range of CD4 + cell counts. Conclusion: ART improved CD4 + cell counts in most children, but the time to CD4 + cell count of at least 500 cells was highly dependent upon baseline immunological status. Some children did not reach a CD4 + T-cell count of 500 cells/μl despite 2 years of virologic suppression. AIDS-defining events occurred in 1% of the population, including children in whom virologic suppression and improved CD4 + T-cell counts were achieved. Abstract : Supplemental Digital Content is available in the text